2020
DOI: 10.1107/s2052252519016142
|View full text |Cite
|
Sign up to set email alerts
|

Crystal engineering of exemestane to obtain a co-crystal with enhanced urease inhibition activity

Abstract: Co-crystallization is a phenomenon widely employed to enhance the physiochemical and biological properties of active pharmaceutical ingredients (APIs). Exemestane, or 6-methylideneandrosta-1,4-diene-3,17-dione, is an anabolic steroid used as an irreversible steroidal aromatase inhibitor, which is in clinical use to treat breast cancer. The present study deals with the synthesis of cocrystals of exemestane with thiourea by liquid-assisted grinding. The purity and homogeneity of the exemestane-thiourea (1:1) co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Crystal engineering approaches for the preparation of APIs and biological compounds significantly improved the physicochemical and biological properties of bioactive compounds (Saha et al, 2014;Kiyonga et al, 2022;Duan et al, 2022). Our research group has reported previously the antileishmanial (Hussain et al, 2018), and urease inhibition (Fatima et al, 2020) properties of bioactive compounds via a cocrystallization approach.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal engineering approaches for the preparation of APIs and biological compounds significantly improved the physicochemical and biological properties of bioactive compounds (Saha et al, 2014;Kiyonga et al, 2022;Duan et al, 2022). Our research group has reported previously the antileishmanial (Hussain et al, 2018), and urease inhibition (Fatima et al, 2020) properties of bioactive compounds via a cocrystallization approach.…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with the theme of 'structure' a number of papers dealt with cocrystals both in the pharmaceutical context (Fatima et al, 2020;Ranjan et al, 2020) and in a more general sense (Rajkumar & Desiraju, 2021). Other areas addressed included charge density (Chodkiewicz et al, 2020;Sanjuan-Szklarz et al, 2020;Duverger-Né dellec et al, 2020), phase transformations (Smets et al, 2020;Rekis et al, 2021), crystals obtained under exotic conditions (Buganski & Bindi, 2021;Hu et al, 2020;Né meth, 2020), and MOFs (Yadava et al, 2020;Park et al, 2020) apart from core papers on supramolecular synthons and synthetic strategy.…”
mentioning
confidence: 99%
“…For comparison, about 150 papers in the crystal engineering area have been published since the inception of the journal itself. Recent papers that have been published in IUCrJ cover a variety of frontier topics and some representative papers are listed below (Alex et al, 2019;Brink & Helliwell, 2019;Broadhurst et al, 2020;Fatima et al, 2020;Gianopoulos et al, 2019;Oburn et al, 2019;Ranjan et al, 2020). These cover areas like charge density, polymorphism and isomorphism, mechanical properties, pharmaceutical solids, and core papers on supramolecular synthons and synthetic strategy.…”
mentioning
confidence: 99%